1998
DOI: 10.1007/bf01900533
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic estimation of postpartum postvoid residual bladder volume: A comparison between transabdominal and transvaginal ultrasonography

Abstract: Postvoid residual bladder volume (PVRBV) was estimated in 89 patients with postpartum urinary retention using two ultrasonographic volume estimation methods. The PVRBV estimated by transabdominal and transvaginal ultrasonography are compared using the plot of difference against mean and the paired t-test. Neither showed any significant difference between the two methods (paired sample t-test, P > 0.05). The two methods have high correlation coefficient of 0.903 (Spearman's correlation, P < 0.0001). Either ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Nineteen studies have assessed the reliability or validity of real time ultrasound assessment of bladder volume. Only three of these addressed validity in post‐partum women 3–5 . However, systematic review of all these studies 6,7 identified a number of methodological inadequacies in their design, conduct and analysis including recruitment bias, lack of blinding and inappropriate statistical analysis, the ideal for this situation being the intraclass correlation coefficient 3,7 …”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nineteen studies have assessed the reliability or validity of real time ultrasound assessment of bladder volume. Only three of these addressed validity in post‐partum women 3–5 . However, systematic review of all these studies 6,7 identified a number of methodological inadequacies in their design, conduct and analysis including recruitment bias, lack of blinding and inappropriate statistical analysis, the ideal for this situation being the intraclass correlation coefficient 3,7 …”
Section: Introductionmentioning
confidence: 80%
“…Yip et al . compared the accuracy of transabdominal and transvaginal ultrasound measurement of post‐partum postvoid residual bladder volume with each other and reported a good correlation with each other (Spearman's correlation coefficient 0.903) 4 . Comparison with a gold standard such as urethral catheterisation was not carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the diagnosis of PUR relies on an accurate estimation of the postvoid residual bladder volume (PVRBV) [5], consensus on a standardized definition of PUR has not been reached. Ultrasound is becoming more widely used for detection of postpartum or postoperative urinary retention because it is non‐invasive and readily available in most obstetric and gynecology units [6–11]. A PVRBV of 150 mL is the volume definition most commonly used for research purposes [2]; in the present study PUR was based on this value using a bladder scan.…”
Section: Introductionmentioning
confidence: 99%
“…Transvaginal ultrasound scan was adopted instead of transabdominal scan because of two reasons: firstly, to minimize discomfort caused by pressure of the abdominal probe on the caesarean section wound, and secondly, to minimize the risk of caesarean section wound infection caused by contamination from the abdominal probe. All the scans were carried out with the patients lying supine and buttocks elevated by a pillow [12].…”
Section: Methodsmentioning
confidence: 99%